The Role of the MyD88/IL-1/IL-1R Signaling Axis and TLR1 Expression in Breast Cancer (MCF7) Cells - Hassoon, Rasha Amer; froushani, Seyyed Meysam Abtahi; Razi, Mazdak (Journal of Neonatal Surgery, 2025)
Background: Breast cancer is a leading health concern among women, with significant clinical heterogeneity and variable treatment responses. Recent research has highlighted the importance of immune-related signaling pathways in tumor development and therapy resistance. This study investigates the role of the MyD88/IL-1β/IL-1βR/TLR1 signaling axis in the MCF7 breast cancer cell line. Methods: MCF7 (luminal A subtype) and Human Primary Dermal Fibroblast (HPDF) cells were cultured and analyzed for viability using the MTT assay. Protein expression of MyD88 was evaluated by Western blotting, while mRNA levels of MyD88, IL-1β, IL-1βR, TLR1, TRAF6, IRAK1, NF-κB, and MAPK components were quantified using qRT-PCR. Data were statistically analyzed using ANOVA with significance set at p < 0.05. Results: MCF7 cells demonstrated significantly higher expression of MyD88, IL-1β, IL-1βR, and TLR1 at both 24 and 72 hours compared to HPDF controls. Upregulation of downstream effectors TRAF6 and IRAK1, along with increased expression of NF-κB and MAPK pathway components (p38 and JNK), confirmed activation of inflammatory and survival pathways. Despite similar viability profiles in MTT assays, molecular analysis revealed that MCF7 cells actively exploit this signaling cascade to support tumor-promoting functions. Conclusion: The MyD88/IL-1β/IL-1βR/TLR1 axis is notably activated in MCF7 breast cancer cells, promoting pro-inflammatory signaling and survival through NF-κB and MAPK pathways. These findings suggest potential targets for therapeutic intervention in hormone receptor-positive breast cancer subtypes.